MAKNA SEMIOTIKA DALAM LEGENDA NUSANTARA SEBAGAI BAHAN PENGEMBANGAN PENDIDIKAN KARAKTER DI SEKOLAH: Penelitian Kualitatif - Listiyana Solihah, Ade; Kuswara; Sulyati, E. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Legends, as part of folklore, have great potential in character education because they are rich in moral values and local wisdom. However, the symbolic meanings in Nusantara legends have not been widely utilized in learning. This study aims to examine the semiotic meanings in five water-themed legends from Astri Damayanti’s Kumpulan Legenda Nusantara and to evaluate their potential as teaching materials for character education in elementary schools. The research employed a descriptive qualitative approach using Charles Sanders Peirce’s semiotic theory (icon, index, symbol). The findings show that these legends contain strong symbolism related to honesty, responsibility, empathy, and loyalty. The stories also have good readability for students, with simple language and clear narrative structures. Based on these results, this study recommends the integration of folklore into the curriculum as a medium for character education based on local wisdom.